Pengaruh Tingkat Pendidikan, Upah Minimum Dan Pengangguran Terbuka Terhadap Tingkat Kemiskinan Di Kabupaten Sarolangun - Muhammad Farhan; Bambang Kurniawan; Ferri Saputra Tanjung (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Poverty occurs when a person or group is unable to achieve a level of economic prosperity that is considered the minimum requirement for a certain standard of living. Poverty is born with the limitations of certain people in meeting their needs. The author identifies the problems of this study as follows: Education affects the poverty rate in Sarolangun Regency, Minimum Wage affects the poverty rate in Sarolangun Regency, and open unemployment affects the poverty rate in Sarolangun Regency. Sample determination in quantitative research The total population is 298,091 people, the population is obtained from the total population data of Sarolangun Regency in 2022 Sarolangun Regency. The number used was obtained as a result of calculations with the Yamane formula totaling 100 respondents. The results of the study are (1) education has a positive effect on poverty, (2) minimum wage has a positive effect on poverty (3) open unemployment rate has a positive effect on poverty.